Finite element modelling and experimental study on static deflection and vibration of piezoelectric composite plates - Thinh, Tran Ich; Ngoc, Le Kim (Vietnam Journal of Mechanics, 2010)
A finite-element model based on the First-Order Shear Deformation Theory is developed for the static flexural shape and vibration control of a glass fibre/polyester composite plate bonded piezoelectric actuator and sensor patches. The piezoelectric’s mass and stiffness are taken into account in the present model. A simple negative velocity feedback control algorithm coupling direct and converse piezoelectric effects are used to actively control the dynamic response of an integrated structure through a closed control loop. The static analysis and active vibration suppression control of a cantilever composite plate are performed as a numerical example to validate the proposed model. The Newmark-\(β\) method is used in the numerical simulation to calculate the dynamic response of the piezolaminated composite plate. The numerical results are presented with discussion and in good agreement with carried out experiments.